Daily profiles of dehydroepiandrosterone and its hydroxylated metabolites with respect to food intake - Stárka, Luboslav; Rácz, Beáta; Šrámková, Monika; Hill, Martin; Dušková, Michaela (Prague Medical Report, 2015)
Eight women of reproductive age with normal body mass index were given 5 standardised meals, and their hormonal milieu was determined during the course of the day. Plasma from 12 withdrawals was analysed for dehydroepiandrosterone and its 7- and 16-hydroxylated metabolites. Overall, there was a maximum in the levels of steroid hormones in the morning, followed by decreases throughout the day. There was also an additional significant decrease found for dehydroepiandrosterone and its 7α-hydroxyderivative in association with the consumption of main meals, but not for the 7β-isomer or 16α-hydroxyderivative.
Keywords: Hydroxylation; přijímání potravy; Drug Administration Schedule; následné studie; hydroxylace; vztah mezi dávkou a účinkem léčiva; Adult; dehydroepiandrosteron; dospělí; Eating; Follow-Up Studies; Adjuvants, Immunologic; lidé; ženské pohlaví; Humans; adjuvancia imunologická; Dehydroepiandrosterone; rozvrh dávkování léků; Female; Dose-Response Relationship, Drug